MODERN ASPECTS OF SEARCHING INCENTIVES TO INNOVATIVE ACTIVITY OF BUSINESS ENTITIES - KOSTETSKYІ Volodymyr; PRYMACHENKO, Ivan (Scientific journal «World of Finance», 2020)
Introduction. In In today’s conditions of economic development, business entities face the challenge of reformatting systems, methods and economic mechanisms for managing sustainability in terms of innovative approach. Therefore, the solution of economic, social, managerial and personal problems in contemporary society implies a specific innovative style of management, which is based on innovation, innovation, systematic and continuous innovation activities. The purpose is to identificatt the positive trends and shortcomings of the processes of innovative development of economic entities that exist in Ukraine, and to clarificate of modern scientific approaches to encourage businesses to innovate in order to ensure financial stability and innovative development of the country’s economy. Results. The study of the mechanism of innovation activity allows us to conclude that the formation and development of an innovative management strategy by an economic entity is an integration process that combines the processes of forecasting, planning and accounting of the resource base of the enterprise in the long-term, medium-term and short-term prospects in the new conditions modernization of the state economy. Creating a national innovation system is to build a holistic system that effectively transforms new knowledge into new technologies, products and services that find their real consumers in national or global markets. At the same time, attention should be paid to the development of an innovative strategy by each domestic enterprise, which will create conditions for positive trends in the development of this process. Conclusions. Innovations are essentially related to the cyclical development of the economy, as they initiate new technological developments. Therefore, in an innovative economy, the state plays an important role in implementing anti-cyclical economic regulation, smoothing out cyclical fluctuations and mitigating their effects. To ensure the further development of innovation in Ukraine, it is necessary to comprehensively use methods to stimulate innovation, in particular the improvement of tax legislation; improving the legal framework for venture funds; improving the mechanism of protection of intellectual property rights; ensuring effective cooperation between the scientific and business sectors in the field of innovation.